Model of Ethical Assessment of Clinical Trials of Medicinal Product after the Entry into Force of Regulation 536/2014 and the Protection of a Clinical Trial Participant – Remarks in the Light of the New Act on Clinical Trials of Medicinal Products for Hum - Rabiega-Przyłęcka, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The aim of the article is to present the model of ethical evaluation of a clinical trial introduced in Poland in connection with the implementation of the EU system for registration of clinical trials of medicinal products. The EU legislator left it to the national law of the Member States to specify the detailed organization of the system of ethical evaluation of clinical trials, which, on the one hand, should ensure a high substantive level of ethical evaluation of a clinical trial, guaranteeing, among others, adequate protection for clinical trial participants, and, on the other hand, efficient assessment of the application for authorization for a clinical trial taking into account the deadlines set out in Regulation 536/2014. The author attempts to evaluate the solutions adopted by the Polish legislator.